Assessment of the insecticidal activity of aqueous extracts of two local plants for the management of Leucinodes orbonalis Guenee, (Lepidoptera : Pyralidae ), pest of eggplant (Solanum aethiopicum), in guinean area of Cote d’ lvoriee - Roi Nondenot, Aboua Louis; Adagba, Obodji (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Leucinodes orbonalis is a major pest of eggplant (Solanum aethiopicum). Control tests with aqueous extracts of two local plants have been carried out on this pest in Azagui located Guinean area of Co´te d’Ivoire. The experimental design used was a randomized block with three replications consisting in total of seventeen sub-plots corresponding to sixteen treatments and untreated control. After spraying with different concentrations of extract, two groups were distinguished in comparison with the chemical insecticide (K-optimal 35 EC). The group of extract witch permitted to obtain the best results than the chemical insecticide was composed of aqueous extract capsules R. communis (50 and 60 g / l). At these concentrations of 50 and 60 g / l, the highest percentage of the reduction of shoot infestation were respectively 94.71 ± 1.12 % and 93.14 ± 0.85 % (stage before flowering), 95.78 ± 1.07 and 94.40 ± 0.76 % (flowering stage) and 94.73 ± 0.86 and 94.22 ± 0.57 % (fruiting stage). As for the higher fruit percentage of the reduction of shoot infestation were respectively 85.68 ± 1.64 % (60 g / l) and 86.80 ± 1.51 % (50 g / l). The highest numbers of healthy fruit ranged from 206.81 ± 6.16 (50 g / l leaves of C. papaya) and 237.10 ± 6.96 10 fruits per plant (50 g / l seed capsule of R. communis). The aqueous extract of the R. communis seed capsule could be used for integrated pest management against L. orbonalis.